How Does Green Investment Influence on Tourism Development in Thailand? - YANG, Xiugang (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).11, 2022)
Based on time series from 1995 to 2020 in Thailand economy, this paper has measured green investment level, social livability degree and tourism industry development, demonstrated the significant positive relation among them. Result shows that green investment level significantly promotes tourism development, here social livability degree plays mediator role completely; some dimensions including health and life investment, green energy input and cyclic utilization take positive role on tourism development, but ecology and environment protection doesn’t play deserved positive role on both social livability and tourism development, there are certain destroying of ecology and decreasing of environment protection as tourism development and social livability goes on.